Workshop Developing Entrepreneurial Spirit Based on Socio-Technopreneurship for Students of SMAN 3 Unggul Sigli - Halim, Hendra; Riyaldi, Muhammad Haris; Kesuma, Teuku Meldi; Siregar, M. Ridha; Ningsing, Diana Setya; Pitaloka, Endang; Amir, Fakhrurrazi; Sari, Meutia Dwi Novita; Syahriyal, Syahriyal; Nisva, Raisa Ullya (Jurnal Pengabdian Bakti Akademisi, 2025)
This community service activity aims to foster an entrepreneurial spirit based on socio-technopreneurship among students of SMAN 3 Unggul Sigli, Pidie Regency, Aceh. The main issue addressed is the low interest and ability of students in entrepreneurship, primarily due to limited exposure to practical and technology-relevant entrepreneurship education. Using the Service Learning (SL) approach, the activity was conducted in the form of a workshop consisting of three main sessions: material presentation, business plan preparation practice, and presentation of results. The participants included 50 students guided by a team from the Program Studi Ekonomi Islam Fakultas Ekonomi Universitas Syiah Kuala and the Pusat Riset Komunikasi Pemasaran, Pariwisata, dan Ekonomi Kreatif Universitas Syiah Kuala. The results showed a significant increase in students' understanding of socio-technopreneurship (from 60% to 85%) and their interest in entrepreneurship (75%). Additionally, 60% of the participant groups successfully developed innovative business plans. This activity contributes to achieving the Sustainable Development Goals (SDGs), particularly in creating decent work and promoting sustainable economic growth.